Hydrothermal carbonization (HTC) of green waste: An environmental and economic assessment of HTC coal in the metropolitan region of Berlin, Germany - Jakob Medick; Isabel Teichmann; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Based on a life-cycle sustainability assessment and the calculation of carbon abatement costs, we quantify the greenhouse-gas emission reductions and costs if green waste in the metropolitan region of Berlin, Germany, is diverted from composting into the production of hydrothermally carbonized coal (HTC coal) that is used as a substitute for hard coal in the generation of electricity and heat. Depending on the geographical origin of the green waste, we specify an urban scenario, a rural-urban scenario, and a rural scenario. Approximately 302 kilogram (kg) of carbon-dioxide equivalents (CO2e) can be saved per megagram (Mg) of fresh-matter (FM) input in the urban scenario, 298 kg CO2e/Mg FM input in the rural-urban scenario, and 316 kg CO2e/Mg FM input in the rural scenario. All three scenarios combined can mitigate a total of 70,511 Mg CO2e per year. This corresponds to about 1.6% of Berlin's annual greenhouse-gas reduction targets over the 2005-2020 period. If only private costs are considered, the HTC scenarios are less profitable than their reference cases. However, the inclusion of emissionrelated damage costs has the potential to render them socially preferable. The respective thresholds for social desirability coincide with the carbon abatement costs, about 163 exteuro/Mg CO2e in the urban scenario, 74 exteuro/Mg CO2e in the rural-urban scenario, and 75 exteuro/Mg CO2e in the rural scenario. The lower abatement costs in the latter two scenarios are due to HTC-coal co-firing in an existing power plant rather than mono-firing it in a newly built biomass power plant. This shows that a comparatively favorable use of HTC coal might be as a bridging technology.
Keywords: Q42; Q51; Q54; 330; hydrothermal carbonization; char; biocoal; climate change; renewable energy; biomass; waste management; life cycle